2023
DOI: 10.1093/cvr/cvad120
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial pannexin1 controls cardiac sensitivity to ischaemia/reperfusion injury

Olga M Rusiecka,
Filippo Molica,
Morten S Nielsen
et al.

Abstract: Aims No effective therapy is available in clinics to protect the heart from ischaemia/reperfusion (I/R) injury. Endothelial cells are activated after I/R, which may drive the inflammatory response by releasing ATP through pannexin1 (Panx1) channels. Here, we investigated the role of Panx1 in cardiac I/R. Methods and results Panx1 was found in cardiac endothelial cells, neutrophils, and cardiomyocytes. After in vivo I/R, serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Another fundamental question is to discriminate between the channel-dependent or channel-independent role of connexins and pannexins in repairing airway epithelial cells. In this context, a particular focus must be placed on their localization, as connexins and pannexins can be found in intracellular compartments [122,144,145]. The intracellular relocalization of connexins and pannexins depends on the regulation of their trafficking and degradation, which are controlled by phosphorylation, acetylation, glycosylation, and ubiquitination [12,146].…”
Section: Discussionmentioning
confidence: 99%
“…Another fundamental question is to discriminate between the channel-dependent or channel-independent role of connexins and pannexins in repairing airway epithelial cells. In this context, a particular focus must be placed on their localization, as connexins and pannexins can be found in intracellular compartments [122,144,145]. The intracellular relocalization of connexins and pannexins depends on the regulation of their trafficking and degradation, which are controlled by phosphorylation, acetylation, glycosylation, and ubiquitination [12,146].…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Release of ATP from cardiomyocytes through PANX1, which caused fibroblast activation in vitro, has previously been described. 16 Moreover, global PANX1 deletion in mice decreased ischemic area in a model of cardiac ischemia-reperfusion injury, 34 while endothelial cellspecific deletion of PANX1 in mice decreased immune cell infiltration in a model of myocardial infarction. 35 Though much of the work done with PANX1 heavily implicates the role of PANX1-dependent ATP release, previous studies have demonstrated that a wide variety of metabolites can be released through PANX1.…”
Section: Novelty and Significancementioning
confidence: 99%
“…Release of ATP from cardiomyocytes through PANX1, which caused fibroblast activation in vitro, has previously been described 16 . Moreover, global PANX1 deletion in mice decreased ischemic area in a model of cardiac ischemia reperfusion injury 34 , while endothelial cell-specific deletion of PANX1 in mice decreased immune cell infiltration in a model of myocardial infarction 35 . While these prior studies have strongly implied PANX1 as a therapeutic target for cardiovascular diseases in general 36 , the role for PANX1 in cardiomyocytes specifically in the regulation of chronic cardiac pathologies, including heart failure, remains to be elucidated.…”
Section: Introductionmentioning
confidence: 98%